Electrospun thermosensitive hydrogel scaffold for enhanced chondrogenesis of human mesenchymal stem cells. (15th January 2018) - Brunelle, Alexander R.; Horner, Christopher B.; Low, Karen; Ico, Gerardo; Nam, Jin
Graphical abstract: Abstract: Hydrogels have shown great potential for cartilage tissue engineering applications due to their capability to encapsulate cells within biomimetic, 3-dimensional (3D) microenvironments. However, the multi-step fabrication process that is necessary to produce cell/scaffold constructs with defined dimensions, limits their off-the-shelf translational usage. In this study, we have developed a hybrid scaffolding system which combines a thermosensitive hydrogel, poly(ethylene glycol)-poly(N-isopropylacrylamide) (PEG-PNIPAAm), with a biodegradable polymer, poly(ε-caprolactone) (PCL), into a composite, electrospun microfibrous structure. A judicious optimization of material composition and electrospinning process produced a structurally self-supporting hybrid scaffold. The reverse thermosensitivity of PEG-PNIPAAm allowed its dissolution/hydration upon cell seeding within a network of PCL microfibers while maintaining the overall scaffold shape at room temperature. A subsequent temperature elevation to 37 °C induced the hydrogel's phase transition to a gel state, effectively encapsulating cells in a 3D hydrogel without the use of a mold. We demonstrated that the hybrid scaffold enhanced chondrogenic differentiation of human mesenchymal stem cells (hMSCs) based on chondrocytic gene and protein expression, which resulted in superior viscoelastic properties of the cell/scaffold constructs. The hybrid scaffold enables a facile, single-step cell seeding process to inoculate cells within a 3D hydrogel with the potential for cartilage tissue engineering. Statement of Significance: Hydrogels have demonstrated the excellent ability to enhance chondrogenesis of stem cells due to their hydrated fibrous nanostructure providing a cellular environment similar to native cartilage. However, the necessity for multi-step processes, including mixing of hydrogel precursor with cells and subsequent gelation in a mold to form a defined shape, limits their off-the-shelf usage. In this study, we developed a hybrid scaffold by combining a thermosensitive hydrogel with a mechanically stable polymer, which provides a facile means to inoculate cells in a 3D hydrogel with a mold-less, single step cell seeding process. We further showed that the hybrid scaffold enhanced chondrogenesis of mesenchymal stem cells, demonstrating its potential for cartilage tissue engineering.